CORROSION INHIBITION EFFECT OF BALANITE AEGYPTIACA LEAVES EXTRACT ON MILD STEEL IN 5M H2SO4 A GRAVIMETRIC AND THERMOMETRIC STUDY - Ahmed, Jibrima; Katagum, Yahaya Muhammed; Sanusi, Abdulrazaq; Nuhu, Awwal Hussain; Juji, Wahiba Ubayo; Babangida, Hassan (FUDMA Journal of Sciences, 2025)
The corrosion inhibition effect of Balanites aegyptiaca leaves extract on mild steel in 5 M sulphuric acid solution has been investigated using gravimetric study and thermometric technique at 40 oC, 50 oC, and 60 oC. The main aimed of this research is to investigate the potential of Balanite aegyptiaca leaves powder for corrosion inhibitition. The Balanite aegyptiaca fresh leaves was obtained from itas Gadau local government Bauchi and the leaves sample was washed and shade dried for two weeks under room temperature The concentration of the inhibition 0.01, 0.02, 0.03 and 0.04 g/L was prepared and used at temperature of 313 K, 323 K, and 333 K respectively. The inhibition efficiency was found to be highest at 313 K and 0.04 g/l concentration of the extract with IE of 18.48 % and lowest at 333 K and 0.01 g/l concentration with IE of 16.42 %. Therefore the Inhibition efficiency increases with extract concentration but decreases with temperature. The thermodynamic parameters and results from the FTIR (shift from 1208 cm-1 to 1205 cm-1 and 1618 cm-1 to 1611 cm-1 and appearance of new 1016 cm-1, 1676 cm-1, 1834 cm-1, 3905 cm-1 bands,” etc) revealed the adsorption of the inhibitor molecules on mild steel surface as comprehensive adsorption involving physical and chemical adsorption. Results show that Balanites aegyptiaca which is biodegradable, environmentally, and are obtained from a renewable resource with minimal health and safety concerns has the potential to a cost-effective alternative to synthetic corrosion inhibitors